2020
DOI: 10.1002/wcc.674
|View full text |Cite
|
Sign up to set email alerts
|

Polarized U.S. publics, Pope Francis, and climate change: Reviewing the studies and data collected around the 2015 Papal Encyclical

Abstract: As soon as it was clear that Pope Francis's 2015 Encyclical, Laudato Si': On Care for Our Common Home, would discuss, among other issues, the moral imperative to address global climate change, U.S. scholars and research institutions rushed to collect data surrounding its release. These groups aimed to determine whether there would be a "Francis Effect," in which U.S. Conservatives (and Conservative Catholics in particular) would show greater concern about the negative effects of global climate change. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Previous studies indicate a rather minor role of religious leaders in promoting the acceptance of vaccination [3]. Along with the fact that not all Catholics respect Pope Francis equally (Political Conservatives view Pope Francis as less credible) [68], it should not be surprising to find negative sentiment towards the pope's encouragement of vaccination.…”
Section: Level Of Trust In Vaccinationmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies indicate a rather minor role of religious leaders in promoting the acceptance of vaccination [3]. Along with the fact that not all Catholics respect Pope Francis equally (Political Conservatives view Pope Francis as less credible) [68], it should not be surprising to find negative sentiment towards the pope's encouragement of vaccination.…”
Section: Level Of Trust In Vaccinationmentioning
confidence: 98%
“…Undoubtedly, Pope Francis is one of the authorities of the modern world. This is due to the office he holds, but also to his personality traits and his conscious effort to have the Catholic Church perceived as an important player in the international arena, and his voice on important issues (such as migration and migration policy or climate change) widely known and commented on [68,78]. Speaking on important topics, Francis is aware of the 'media' power of gestures and sentences [79].…”
Section: Appendix a Appendix A1 The Pope And The Vaccination Issuementioning
confidence: 99%
“…For example, respected religious leaders, such as popes, may help increase the effects of stewardship messages among religious individuals. Schuldt, Pearson, Romero‐Canyas, and Larson‐Konar (2017) showed that a brief exposure to Pope Francis increased perceptions of climate change as moral issues, especially when respondents were aware of his views on climate change (i.e., urging the global community to take climate action; see also Landrum & Vasquez, 2020). Employing religious leaders as messengers may help increase support for environmental action, especially among politically conservative religious people who may find environmental messages inconsistent with their political identities (Gromet, Kunreuther, & Larrick, 2013; Landrum, Lull, Akin, Hasell, & Jamieson, 2017).…”
Section: Communications and Interventions Leveraging Stewardshipmentioning
confidence: 99%
“…In recent times, Pope Francis' Laudato Si (2015) was the most influential work for 'caring for our common home' which was issued a few months before the commencement of the Paris Climate Summit. The encyclical, addressing the global audience, framed the climate crises from a moral position, linking the climate crises and global economic inequality (Landrum & Vasquez, 2020). The encyclical aimed at the environmental discourse across politicians, economic organizations, religious leaders, intellectuals, academicians and the common public.…”
Section: Environmental Communication: Socio-political and Economic Pe...mentioning
confidence: 99%
“…To achieve sustainable behavior and sustainable development, what is required is not just scientific knowledge about climate change but a change in ethical and moral perspectives, attitudes and a shift in political ideology that would promote welfare economics (Landrum & Vasquez, 2020). For many people, as scientific facts could be ideologically inconvenient, the truth is brushed away on political and economic interests and the needed action is opposed (Mann, 2021).…”
Section: Ideological Shiftmentioning
confidence: 99%